Prognostic factors influencing the outcome of empyema surgical management: prospective study in a Moroccan university center. - hafidi, Sara; Boubia, Souheil; Fatene, Abdellah; Id El Haj, najat; Ridai, Mohammed (British Journal Of Surgical Science, 2021)
Background: Pleural empyema is a public health problem, and is the most frequent complication of pleural infection with significant morbidity and mortality worldwide. Our study aims to highlight the management of pleural empyema and evaluate its prognosis factors involved especially in surgical treatment. Patients and Methods: A prospective analysis of 53 patients who underwent surgical treatment of pleural empyema, from January 2015 to December 2019 at the thoracic surgery department in a tertiary referral university teaching hospital. Our study included patients who required surgical treatment for pleural empyema and were excluded patients with destroyed lungs associated with pyothorax. Results: The mean age of patients was 39.24±15.89 years and 79,24% of them were males. In 85.7% of the cases, the etiology was undetermined in 34%, parapneumonic in 1.9%, of tuberculosis in 54.71%, post-traumatic in 11, 3%, postoperative in 7.5% and iatrogenic in 1.9%. 45 patients were treated with broad-spectrum antibiotics therapy adapted after antibiogram 14.38±21.76 days before the operation. A complete debridement and decortications were performed by VATS in 28 and by PLT in 22 patients. No major complications occurred. At a mean term follow-up of 20 months (3months—3 years); all patients were alive with no recurrence. The analysis of the results showed 4 factors of poor prognosis: delay of diagnosis and surgery (P = 0.02), chronic alcoholism (P = 0.034), preoperative ventilation disorder/COPD (P = 0.04) and active tuberculosis (P= 0, 05). Conclusion: The success of surgical management of pleural empyema depends on several factors, which predict the prognosis, but can be prevented.